Ophthalmological complications of the new coronavirus infection COVID-19. Clinical cases - E. A. Latypova; A. Sh. Zagidullina; T. R. Mukhamadeev; M. A. Gizatullina; A. G. Yamlikhanov; G. F. Khairullina (Российский офтальмологический журнал, 2024)
The outcomes and complications of the coronavirus infection are of interest to specialists in many fields of medicine, including ophthalmologists.Purpose: to analyze the clinical features of ophthalmic complications in patients with coronavirus infection COVID-19.Materials and methods. Four patients aged 37 to 70 years with ophthalmic inflammatory complications with coronavirus infection were examined and treated.Results. In 2 cases, eye damage was observed in the acute phase of COVID infection. It included deep keratitis, iridocyclitis, and exacerbation of rhinosinusitis complicated by osteomyelitis, orbital phlegmon with loss of vision. In the remaining 2 cases, in the post-COVID period (2 and 5 months after the disease, respectively), acute dacryoadenitis with the dry eye syndrome and subacute episcleritis was observed. In addition to anti-COVID therapy, all patients underwent specific ophthalmic therapy, which in 1 case included surgical intervention.Conclusion. The cases presented demonstrate eye damage against the background of coronavirus infection with the involvement of various eye structures into the inflammatory process. The ophthalmological manifestations were severe, with complications in the acute phase of COVID and in the early post-COVID period. Clinical observations indicate the need for additional specific therapy of coronavirus infection complications, along with the basic anti-COVID treatment.